Benefits of building information modelling in mitigating claims and disputes of construction projects in Jordan - Saraireh, Ibrahim Moh’d; Suleiman, Akram; Al Biajawi, Mohammad I.; Alziadin, Saleem (Archives of Civil Engineering, 2026)
Claims play an important role in construction projects as they can have a significant financial impact that can affect the overall cost and schedule of the project. The introduction of Building Information Modeling (BIM) is changing the traditional methods of the construction industry and has strengthened the influence of the planning process on the entire life cycle of a construction project. Therefore, this research attempts to identify the function of Building Information Modeling (BIM) in mitigating such claims and disputes. To achieve the aim of this research, 380 assessments done by industry specialists were examined using the mean ranking method, the normalization process, the RII and factor analysis. The results of this study quantify the main causes of claims and disputes associated with the contractor and owner, such as financial problems of the contractor (RII 0.792), delays caused by the contractor (RII 0.784), delays in payment of completed work to the contractor (RII 0.794), oral change orders from the owner (RII 0.790). In addition, the results revealed several potential benefits of BIM that include efficient communications between stakeholders (RII 0.852), better visualization (RII 0.846), 3D-Coordination and clash detection (RII 0.830). This survey contributes to the current form of information by identifying the main sources of disputes and claims in projects. In addition to revealing the benefits of BIM that industry experts can use to improve project performance.